THE IMPACT OF STOCK SUSPENSION ON PUBLIC INVESTOR PROTECTION IN THE INDONESIAN STOCK EXCHANGE - Muhammad Rangga Arya Putra; Gatot P. Soemartono (EKSEKUSI, 2025)
This study aims to examine the impact of stock suspension policies on the protection of public investors in the Indonesian capital market. This study uses a normative juridical approach by examining laws and regulations related to the capital market sector. A comparative approach is also used by reviewing regulatory practices in Malaysia to identify normative and procedural gaps in the suspension mechanism in Indonesia. The results of the study show that stock suspension serves as an instrument to maintain market integrity, but in practice it can limit investors' rights to liquidity and information disclosure if it lasts too long without clear reasons and time limits. Compared to Malaysia, Indonesia does not yet have a definite deadline, creating legal uncertainty for public investors. This article provides solutions to the stock suspension mechanism within the framework of Indonesia's capital market law by emphasizing clearer coordination between supervisory agencies and strengthening information disclosure obligations.